(untitled) (مجلة العلوم الإنسانية المرقب, 2024)
The current study investigated the most common punctuation errors made by second year students at English Department at ELMergib University. It also sought to find out the reasons behind committing such errors and to suggest some solutions. The selected instrument for this research was a test. The test included 18 different kinds of sentences missing some punctuation marks, and students needed to apply the proper punctuation mark in its right place. The sample was taken from second year level. The participants were 18. The data was analyzed both qualitatively and quantitatively. The results of the study indicated that the second year students committed a large number of errors. They faced difficulties in the use of punctuation marks properly and effectively. The colon was the most difficult mark for subjects. In addition, the results of this study revealed that most errors were attributed to lack of knowledge which could be as a result to the lack of practice. The researchers have recommended the teachers and students to pay more attention to the punctuation marks and give more emphasis to the practice.